2014
DOI: 10.1016/j.watres.2013.09.024
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial pesticide removal in rapid sand filters for drinking water treatment – Potential and kinetics

Abstract: Filter sand samples, taken from aerobic rapid sand filters used for treating groundwater at three Danish waterworks, were investigated for their pesticide removal potential and to assess the kinetics of the removal process. Microcosms were set up with filter sand, treated water, and the pesticides or metabolites mecoprop (MCPP), bentazone, glyphosate and p-nitrophenol were applied in initial concentrations of 0.03-2.4 μg/L. In all the investigated waterworks the concentration of pesticides in the water decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…However, an adaptation phase of more than 16 days is required before MCPP degradation is initiated in aquifer material (Agertved et al, 1992;Tuxen et al, 2000;Janniche et al, 2010). Filter sand that has not previously been exposed to pesticides is able to remove pesticides without an adaptation phase (Hedegaard and Albrechtsen, 2014) and in the current laboratory experiments degradation of MCPP was also initiated immediately ( Figure 7). However, the secondary filters at Kerteminde Waterworks had been exposed to concentrations of MCPP for at least nine years prior to these investigations (Figure 1).…”
Section: Perspectivesmentioning
confidence: 65%
See 2 more Smart Citations
“…However, an adaptation phase of more than 16 days is required before MCPP degradation is initiated in aquifer material (Agertved et al, 1992;Tuxen et al, 2000;Janniche et al, 2010). Filter sand that has not previously been exposed to pesticides is able to remove pesticides without an adaptation phase (Hedegaard and Albrechtsen, 2014) and in the current laboratory experiments degradation of MCPP was also initiated immediately ( Figure 7). However, the secondary filters at Kerteminde Waterworks had been exposed to concentrations of MCPP for at least nine years prior to these investigations (Figure 1).…”
Section: Perspectivesmentioning
confidence: 65%
“…The complete removal in Filter line 1 might simply be due to a longer reaction time in the filter; otherwise, the longer contact time could cause greater biomass and thereby the increased microbial degradation of MCPP in the filter. Other research has also indicated that longer contact time has a positive effect on the removal of micro pollutants in rapid sand filters (Hedegaard and Albrechtsen, 2014;Zuehlke et al, 2007).…”
Section: Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…Apart from bacterial contamination, pesticides in water are also a major concern. In a recent study, Hedegaard et al (40) investigated the effect of rapid sand filters for treating contaminated groundwater at three Danish waterworks. They found that the filters could effectively remove pesticides such as bentazone, glyphosate, and p-nitrophenol.…”
Section: Filtrationmentioning
confidence: 99%
“…A biofilter with granular filter materials has been considered as a viable option for drinking water treatment, allowing for microorganisms in the source water to attach to the media surface [13]. It had been reported that various kinds of emerging organic pollutants could be removed in biofilters, including geosmin [14], 17β-estradiol [15], mecoprop, bentazone, glyphosate, p-nitrophenolat [16], dimethylamine [17], and carbofuran [18], etc. Although granular activated carbon (GAC) has been widely used as filter media [14][15], its high cost and potential loss during backwashing are hurdles for its direct application in a rapid filter.…”
mentioning
confidence: 99%